Out of the Frame: The Essay Writing of Oscar Wilde and Virginia Woolf (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
The paper examines selected essays by Oscar Wilde and Virginia Woolf within the social, cultural and artistic context at the turn of the century. The essay, which implies a note of subversion, proves to be the ideal form for these two writers, who have a chameleonic ability to disguise, deceive and seduce the reader. Although apparently Wilde and Woolf had no common points of contact either in life or in literary creation, the analysis of their essays in which they clearly present their view of art and the criticism of the traditional approach to the literature of their contemporaries, in which realism served as a mirror of social reality, points to numerous similarities in understandings of art. Firstly, the influences of Walter Pater and Shakespeare on both authors are analysed, and then the viewpoints regarding the perception of art are compared. Both authors despise the photographic approach to literature, the superficial realism that relies on descriptions, and demand a turn to inner experience, contemplation and memories, looking for a new stylistic expression as well. Satire, which is more pronounced in Wilde, but also present in Woolf, serves as a means of criticizing the traditional patriarchal society, with which both authors point to social problems, and, additionally, in Woolf, to the problems of gender inequality. Both authors have utopian ideas about an ideal society, but at the same time they are aware that they are unrealistic and unachievable. Wilde and Woolf demand the noninterference of politics and morality in literature, they claim it is inappropriate to use literature for political or any similar purposes. Wilde’s aestheticism and decadence represent a step towards a new approach and understanding of art, which will contribute to the development of modernism. His idea of art for art’s sake influenced the aesthetics of the time, just as the modernist views of Virginia Woolf expressed in her essay A Room of One’s Own influenced the artistic climate at the beginning of the twentieth century. She demanded a break with the realistic style of writing, as well as with the traditional understanding of gender roles. Wilde’s claim that life imitates art far more than art imitates life implies that the artist uses his personal experience in creating art and reshaping it, affirming that in every art there is a part of the life of the artist who created it. It is the artist who gives life to beauty. Wilde and Woolf oppose imitation, art requires originality and passion, and each artist seeks his own expressive form, unique and individual. Wilde does not believe in a firm division of genres, but that literature tends to create new genres. Accordingly, Woolf was an advocate of experimental methods in literature, the search for new and original expression, she even tried, albeit unsuccessfully, to write a “novel-essay”. Wilde and Woolf also show similarities regarding the reversed role of reader/critic and writer in the literary process of creation, where the emphasis is placed on the artistic aspect of criticism, that is, reading in order to create new, richer and more diverse works of art. Both authors significantly contributed to the modernist movement, a new understanding of reality, autonomy in the artistic process and individualism. At the same time, their works express the inner experience of people with silenced voices and marginalized in a society that denied them being who they felt they really were. Their suppressed voices of marginalization and otherness had to remain hidden due to strict traditional social norms of the Victorian era.
Keywords: essay writing; aestheticism; literary criticism; subversion; modernism